Mobile Application for Learning and Memorizing Japanese Characters using Game-Based Learning - Mohd Rozi, Nor Aizie Izzaty; Ahmadon, Fadzlin; Mohamed Aris, Ruzana; Mohd Hizal, Muhammad Haziq; Maarof, Haziq Iqbal (2020)
The Japanese language has three writing system which are Hiragana, Katakana, and Kanji. To help with the pronunciation of Hiragana and Katakana characters, they include special accented characters known as 'Dakuten' and 'Handakuten'. However, most students have difficulties in remembering and recognizing Hiragana and Katakana characters and how these characters can be pronounced. Therefore, a game was developed to help students in memorizing, recognizing the different symbols of Hiragana and Katakana character, and increase a better understanding of them. This project uses the ADDIE model as a framework in Methodology because the model is commonly used in educational and instructional design development. The game involves two types, the first one is Memory Song Game and the second one is Match Puzzle Game. The game's theme is 'Pirate' where the player needs to find the character that matches the puzzle space while memorizing the characters through Game-Based Learning principle. Thirteen students in UiTM Jasin Melaka who are learning the Japanese language and who are also planning to take Japanese as a third language are involved to test the usability of the game. The majority of the respondents are satisfied the game is beneficial and good in the enhancement of learning in the Japanese language. It was discovered that they enjoyed the challenging part of the game. In conclusion, this project has successfully achieved all three objectives that have been identified at the beginning of the process